Heterogeneities, asperities, fluid migration and seismicity - BONAFEDE, MAURIZIO; R. Stefansson (Husavik Academic Center, 2014)
The models presented below explain several features of the preparatory processes leading to the M = 6.6 earthquake of June 17th 2000 in the SISZ (Stefansson et al., 2011). Strong similarities between the SISZ and the TFZ encourage to apply a similar conceptual model to describe the preparatory processes expected to take place before the next large earthquake in North Iceland.